Two new Brazilian species in the Coelocephalapion nodicorne species-group (Brentidae, Apioninae, Apionini, Oxystomatina) associated with Euphorbiaceae - de Sousa, Wesley Oliveira; Anderson, Robert S. (Zootaxa, 2022)
Two new Brazilian species of the genus Coelocephalapion Wagner, 1914 placed in the C. nodicorne species-group (Brentidae: Apioninae) reared from Euphorbiaceae are described and illustrated: Coelocephalapion paleariae sp. n. (Type locality: Botucatu, São Paulo state; reared from seeds Croton glandulosus L.) and Coelocephalapion geraldinhoi sp. n. (Type locality: Dores do Indaiá, Minas Gerais state; reared from leaf galls on Croton antisyphiliticus Mart.). Aside from species descriptions, we also provide a key to species of the C. nodicorne species-group.